Socioeconomic Status and Healthcare Support on Anti-Tuberculosis Medication Adherence Among Pediatric Tuberculosis Patients - Nissa Prima Sari (Frontiers on Healthcare Research)
Background: Tuberculosis (TB) remains a major public health challenge, particularly among children in low- and middle-income countries. Adherence to anti-tuberculosis (anti-TB) medication is essential for treatment success, but socioeconomic factors and healthcare support significantly influence adherence rates. This study examines the association between socioeconomic status (SES), healthcare support, and medication adherence among pediatric TB patients in Solok, West Sumatera, Indonesia.